(untitled) (Research, Society and Development, 2021)
The development of new drugs used to combat and control microorganism’s remains significant in the global scientific context, with natural products, including plant products, being potential sources of new antibacterial and antifungal agents, thus the purpose of this work was to determine the antimicrobial activity of Piper species by bioautography. Antimicrobial activity was performed using the bioautography method, where plates were previously prepared using the thin layer chromatography technique by eluting the crude ethanolic extract (CEE), hexane fraction (HEX) and/or chloroform fraction (CHCl3) of P. caldense, P. arboreum and P. mollicomum, in order to separate the components. The chromatography plates were tested against four standard strains American Type Culture Collection: Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853 and Candida albicans ATCC 76645, the activity being determined by the formation of zones of inhibition in Agar. It was possible to verify that both the CEE and the HEX fraction of Piper caldense showed activity against the S. aureus strain, presenting the place of activity of the chromatoplate, these products did not show activity in relation to the other strains studied. The extracts and fractions of Piper arboreum and Piper mollicomum showed no activity in relation to the studied strains. From the results it is possible to conclude that Piper caldense has potential antibacterial activity against S. aureus. The importance of future studies to identify the active substances and their content in each part of the plant is emphasized.